2014
DOI: 10.1088/1748-9326/9/4/045007
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variations in Sr and Nd isotopic ratios of cryoconite on Asian glaciers

Abstract: Cryoconite is a dark-coloured surface dust deposited on glaciers that consists of wind-blown mineral particles, as well as organic matter derived from microbes living on glaciers. In this paper, we analyse the Sr and Nd isotopic ratios of four mineral fractions (i.e., the saline, carbonate, phosphate, and silicate mineral fractions), as well as the organic fraction, of cryoconite samples obtained from six Asian glaciers (the Altai, Pamir, Tien Shan, Qillian Shan, and Himalayan regions), and discuss their geogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Figure shows the comparison of Nd‐Sr isotopic ratios of cryoconite on the Tibetan Plateau with previous cryoconite data from central Asia (see Figure , compared with the data of Nagatsuka et al []). The colored triangles in the figure show the ratios of loess, sand, and stream sediments from Asia, including the values of North China and Junggar [ Honda et al , ; Nakano et al , ], the Taklimakan desert, southern Gobi desert and the Loess Plateau [ Chen et al , ; Honda et al , ; Nakano et al , ; Yang et al , ], and the Himalaya [ Najman , ; Xu et al , ] and the northwest Indian arid areas [ Tripathi et al , ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the comparison of Nd‐Sr isotopic ratios of cryoconite on the Tibetan Plateau with previous cryoconite data from central Asia (see Figure , compared with the data of Nagatsuka et al []). The colored triangles in the figure show the ratios of loess, sand, and stream sediments from Asia, including the values of North China and Junggar [ Honda et al , ; Nakano et al , ], the Taklimakan desert, southern Gobi desert and the Loess Plateau [ Chen et al , ; Honda et al , ; Nakano et al , ; Yang et al , ], and the Himalaya [ Najman , ; Xu et al , ] and the northwest Indian arid areas [ Tripathi et al , ].…”
Section: Resultsmentioning
confidence: 99%
“…The isotopic ratios showed no significant variation between the sites, suggesting that the mineral dust was derived from a single source and deposited uniformly across the ice surface. Nagatsuka et al (2014b) also showed geographical variation in the isotopic ratios of cryoconites on Asian glaciers, which revealed that the sources of minerals differ among the northern, central, and southern regions in Asia. Therefore, the Sr and Nd isotopic ratios of the minerals in cryoconite could reveal geographical, regional, and altitudinal variation in the mineral sources on the Greenland Ice Sheet.…”
Section: Introductionmentioning
confidence: 92%
“…The sediment size effect suggests that a greater understanding of sediment provenance and transport history should be sought. For example, Nagatsuka et al (2014) showed how the long-range transport of fine aeolian particles may be established using their rare earth element composition and then used to understand bioflocculation into Asian cryoconite. Future work should therefore integrate the techniques described above to understand better the linkages between sediment provenance and microbial diversity.…”
Section: Ice Surface Habitatsmentioning
confidence: 99%